Analyzing the brainwave signals between resident and non-resident students of UiTM for alpha, beta, theta and delta frequency band / Intan Suraya Ismail - Ismail, Intan Suraya (2014)
This research studies on the analyzing the brainwave signals between resident (R)and non-resident (NR) students in the hostel of Universiti Teknologi MARA (UiTM)by using EEG. There are four states of brainwave which are beta, alpha, theta and delta. In this research, all four states of brainwave were focused. This research was conducted on 30 samples (15 R and 15 NR) and they were interviewed. Then, their brainwaves were captured using EEG and graphs were plotted. All data needed were recorded and then analyzed using SPSS software. The data was interpreted using Paired T-test to show correlation between left and right brainwave. Based on the results pretended, it can be concluded that non-resident student's brainwave is not in balance condition and resident student's brainwave are mostly in balance state. For both residencies, they are in right brain dominant.